ANALYSIS OF RETAINING WALL SOIL RETAINING WALL IN THE DEVELOPMENT OF AGRICULTURAL LAND IN THE CENTER OF CLASS I BALIKPAPAN CITY - KARTANEGARA, RIZKY ALAM (KURVA S JURNAL MAHASISWA, 2017)
stability due to disruption of the amount of land on the move it apart from its geometric depends on the severity and also of the shear strength (shear strength). The shear strength is not fixed, and may decline due to rising water levels in the soil itself, in addition to the influence of other disorders. Disruption to the stability of the slope can be caused by nature and by human activity itself. The first thing called natural disasters, which can be caused by earthquakes or heavy rains prolonged, the second is human error, and generally in the form of imposition of excessive (overloading), excavation uncontrollable, drainage is less than perfect, and deforestation. Balikpapan City is one of the areas that have topography wave. On agricultural quarantine hall class I cities Balikpapan particularly in agriculture laboratory balai have a wave in question is a natural state of hills and valleys, this has resulted in some segments of roads must be on the slopes. The presence of natural factors, especially rain and ground water flow that makes it lose ground slope stability or ability to withstand shear, causing landslide, automatically laboratory will be impaired and will also affect the level of service. So that public facilities can function optimally we need to hold the handling of the avalanche is one of them by making the construction of retaining soil so that the soil on these segments do not move or shift. From the results of calculations can be concluded that, the dimensions of retaining wall that is built is 3 meters wide and 2.5 meters, 0.50 meters thick plate with a length of 16 and 26 meters, retaining wall stability is secured against rolling but affect the shear, so that the necessary foundation pile stake to meperkaku wall structure and pile foundation.